(untitled) (European Journal of Engineering Science and Technology, 2020)
Columns, being a very important component of the building structure, are required to be strong enough and also sufficiently deformable to withstand all possible static and dynamic loads to maintain the integrity of the structure throughout their entire life. The strength and the deformability of the columns can be increased by confining the concrete with lateral reinforcements provided in the form of the spirals, hoops or ties. Several experimental and analytical studies have been carried out by various researchers over the years to determine the extent of improvement that can be made to the strength and ductility of the columns, subjected to concentric loading, by confining them using lateral reinforcements. In the present study three-dimensional finite element models of confined concrete columns have been made using ANSYS and analyzed under the application of static concentric loading to find out the effects of lateral confinement. Suitable material models for both concrete and steel have been chosen and nonlinear finite element analysis (FEA) of laterally confined three-dimensional concrete column models have been carried out. The numerical methodology, at first, has been verified against previous experimental results. Then different types of lateral confinements have been modeled and the stress-strain responses and the complex stress distribution patterns have been studied and compared to find out the better type of confinement.